WALL HOSCHMENZIL IN THE VALLEY RUBAS - Gmyra, Ludmila Borisovna (History, Archeology and Ethnography of the Caucasus, 2021)
The Khoshmenzil Wall is a new archaeological site discovered in the lower reaches of the river. Rubas, on the northern outskirts of the village. Rubas of Derbent region of the Republic of Dagestan. It received its designation from the old name of the village located in the place of its location - with. Hochmenzil [Nice place]. The archaeological site is the 6th section of a stone wall preserved on a country road in the northern outskirts of the village. Rubas. The article presents materials from the exploration excavations of this monument, carried out in 2020. The purpose of the research was to determine the functional belonging of the construction site, establish its dating and possible belonging to the barrage defensive line noted in written sources of the mid-18th century. in the lower reaches of the river. Rubas. The relevance of the study was due to the development of the problem of the structure and layout of a large defensive complex of the middle of the 6th century. - Rubas fortification, located 2 km to the west on the left bank of the river. Rubas. The tasks of excavating a new archaeological site were to identify the structure and layout of the structure, to determine the technology of its construction and the degree of preservation. The construction is a section of a stone wall, erected by armour-clad technique from processed stone blocks. The southern facade of the wall with a length of 3.6 m and an adjoining section of backfilling, including torn stone and lime mortar, have been preserved. The stone blocks of the wall are installed using the "poke-spoon" technology. The base of the wall is placed on a stone fill, consisting of torn stone, filled with lime mortar. The height of the preserved section of the wall is 0.6 m. The section of the wall is located on the left bank of the river, it is oriented along with its channel (W – E). The preliminary dating of the monument was determined by the features of the facade design and masonry technology within the middle of the 6th century.